Analysis of evolutionary process in higher education quality in the context of transformation economy - Fang , Jing; Peng , Jie; Cheng , Xinru; Zhang, Chonghui (Transformations In Business & Economics, 2026)
The development level of higher education is a significant indicator of a country’s development strength and potential, as well as a crucial support for the promotion of economic transformation and upgrading. To achieve a more profound understanding of higher education quality in the context of transformation economy, this paper analyses a total of 1,616 papers retrieved from the Web of Science (WoS) from multiple perspectives. The present study analyses the evolution of the common keywords in order to identify hot topics in different periods. By combining citation network analysis and burst detection methods, this study identified the core literature and knowledge diffusion pathways in the research field. The characteristics of centralisation and diversification in higher education research topics were examined by employing strategic analysis. Finally, the study discussed the limitations of current research and the proposed directions for future exploration. This paper provides scholars with an overview of the development process in the higher education domain under transformation economy background, thereby facilitating a comprehensive grasp of the state-of-the-art research.
Keywords: transformation economy; higher education; keywords; burst analysis; strategic analysis